TỔNG HỢP HẠT NANO PHÁT QUANG CePO4:Tb TRONG DUNG MÔI NHIỆT ĐỘ SÔI CAO BẰNG PHƯƠNG PHÁP THỦY NHIỆT - Lộc, Đinh Xuân; Vũ, Nguyễn (Vietnam Journal of Chemistry, 2012)
CePO4:Tb luminescent nanoparticles were successfully synthesized by hydrothermal method in high-boiling solvents such diethylene glycol (DEG) and tris(2-ethylhecxyl)-phosphate (TEHP) at 200oC for 4 hours. FESEM images show that synthesized nanoparticles are uniform in size and spherical in shape with a diameter about 20-50 nanometers. Results from X-ray diffraction patterns exhibit the phase structure of materials are monazite CePO4:Tb with monoclinic structure. CePO4:Tb nanoparticles emit strongly in green region under 325 nm excitation wavelength from the He - Cd laser. The photoluminescent spectra are described by using the well-known 5D4 - 7FJ transitions (J = 6, 5, 4, 3) of Tb3+ ions. The influence of synthesis time maintaining response to morphology, crystal structure, and fluorescence of nanomaterials will be discussed.